Iodometric Estimation of Sucrose in Purified Duck Embryo Vaccine for Rabies - GUPTA, R.N.; SINGH RATHORE, GARVENDRA; KUMAR BASNIWAL, PAWAN (Asian Journal of Chemistry, 2010)
A simple and rapid iodometric titration method was developed and validated for the determination of sucrose in purified duck embryo vaccine for rabies. The lyophilized formulation of rabies vaccine containing NMT 25 mg sucrose per vial was detected by iodimetry titration. The formulation containing sucrose, on acid hydrolysis gives glucose, which can be estimated by iodometric titration. The percentage RSD was found to be NMT 10 %. The method was linear over the concentration range from 60 to 140 % of target concentration (25 mg per vial) with coefficient of correlation 0.9997. Accuracy and precision results were in acceptable limit.